Perancangan Game “IM HERE” Berbasis Augmented Reality dan Location Based Sebagai Media Promosi - Arief Kurniawan Yoga Dywa; RB Hendri Kuswantoro (Journal of Animation and Games Studies, 2020)
On a business there must be advertise for a product, services, and also for entertainment. Advertisement activities has been changed from door to door advertisement to technological advertisement. Technology that used for advertisement are televisions, web and social media. One of the new technology and media that use for advertisement are games. Games as advertisement tool use ads via monetizing and promote services. Some company use augmented reality and location based technology which new technology as advertisement enhancement to attract costumer. Augmented reality is technology that combine real world object and game object, and location based is technology that determine user location in the point of world as coordinate or place descriptions. Augmented reality and location based can be implemented using Unity3D algorithm through accessing user camera and gps. Location based can be implemented as marker for some feature to active if company that want advertise their product or place, user must get profit from activating the feature. Using augmented reality and location base as gameplay may give new experience for user and attract new user or customer.